Design of Ground Penetrating Radar Antenna for Monitoring Soil Contamination at L Band Frequencies - T.Yathavi; B.Premalatha; K.M.Priya; I.S.Akila (International Journal of Engineering and Management Research, 2023)
A major concern for oil companies is the maintenance of oil pipelines. The contamination of the soil is caused by oil leaks from underground pipelines. Using GPR, contaminated soil sites can be located and characterized rapidly and relatively inexpensively without fracturing or spreading contamination. The antenna system is one of the most critical hardware components for GPR performance. To detect soil contamination, an L-band pyramidal horn antenna is designed and simulated at frequencies between 1 and 2 GHz. Modelling the electromagnetic fields in different soil types is done using a prototype GPR system setup. In order to carry out simulations during the design process, the dielectric permittivity of soil is measured and analytically represented by the Debye relaxation model. It is most important to detect contamination by comparing the dielectric permittivity of contaminated and uncontaminated soils. In terms of investigating soil contamination, GPR has proven very successful.